Dakwah Bil Hal as a Method of Dakwah in Society Muneng Ledokdawan Village, Grobogan Regency - Sunarso, Budi (Budapest International Research and Critics University, 2021)
This paper aims to determine the effectiveness of Bil Hal's da'wah in the community of Muneng Ledokdawan village Grobogan District. Namely da'wah that can improve the quality of faith as well as the quality of life of the target da'wah. Da'wah is an obligation of Muslims, so it must be adjusted to the limits of each individual's ability. The selection of methods must be right so that da'wah is right on target. Efforts to approach Islamic teachings can be carried out with 3 approaches, namely oral (bil-lissan), written (bil-risalah), and actions (bil-hal). The content of this paper is in the form of da'wah activities that apply the bil hal approach. For example, congregational prayers, regular recitations once a week (Saturdays), and teaching local women to take care of corpses. The teacher's strategy is to provide an understanding in advance of the activities to be carried out.